PENERAPAN MODEL COMPLETE SENTENCE PADA MATERI MAKANAN SEHAT DAN BERGIZI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE - Gusti Handayani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to determine the improvement of student learning outcomes on healthy and nutritious food after students learn through the Complete Sentence model. The research method used is Classroom Action Research. It consists of two cycles with the steps of planning, acting, observing and reflecting. The population of this study was 4th grade students with a total of 19 people consisting of 7 male students and 12 female students. The results showed that the acquisition of students' scores with the average value and the percentage of completeness according to the cycle was 68.1 or 42% in the first cycle and 89.2 or 100% in the second cycle. Thus, it can be concluded that the application of the Complete Sentence model can improve student learning outcomes.